The effect of Indian jujube leaves extract in inhibiting the growth of Porphyromonas gingivalis - Pratiwi, Gracia Yodianvi; Mandalas, Henry Yonatan; Sugiaman, Vinna Kurniawati (Universitas Padjadjaran, 2022)
Introduction: Periodontitis is an inflammatory disease that destroys tooth-supporting tissues and is associated with increased risk factors for systemic diseases. The main pathogen of periodontitis is the bacteria P. gingivalis, a Gram-negative, anaerobic, pleomorphic, coccobacillus, non-motile, and saccharolytic. The leaves of Indian jujube (Ziziphus mauritiana Lam.) have the main bioactive compounds such as saponins, tannins, and flavonoids which have antimicrobial activities against pathogenic microorganisms. This study aims to analyse various concentrations of the ethanol extract of Indian jujube leaves against P. gingivalis. Methods: The method used in this study was the disc diffusion test based on the Clinical and Laboratory Standard Institute. P. gingivalis preparation and the fresh leaves of Indian jujube collected from one of the plantations in Probolinggo, East Java. In this study, tests used various concentrations of Indian jujube leaves extract, namely 10, 20, 30, 40, 50, 60, 70, 80, 90, and 100%. Data antibacterial activity was classified according to David and Stout’s inhibition zone classification. Results: Indian jujube leaves extract with a concentration between 10-30% had weak antibacterial activity, 40-60% had moderate antibacterial activity, and 70-100% had strong antibacterial activity. The largest inhibitory zone diameter against P. gingivalis was found at a concentration of 100%. Conclusion: Indian jujube leaves extract starting from a concentration of 70% can inhibit the growth of P. gingivalis with strong antibacterial activity.